Penerapan Data Mining Decission Tree Algoritma C4.5 Untuk Mengetahui Tingkat Kepuasan Mahasiswa Terhadap Layanan Akademik Dan Kemahasiswaan (Studi Kasus Universitas.Prof.Dr. Hazairin,SH) - Reni Kurniah; Dadang Yunika Surya Putra; Elviza Diana (Fakultas Teknik Universitas Hamzanwadi, 2022)
Measuring the level of student satisfaction with academic and student services really needs to be done by measuring the level of student satisfaction with academic and student services that can be used as a benchmark for the quality of services that have been provided. By knowing the level of student satisfaction, the university can improve the service if it is not good and further improve the service if the satisfaction level is good. The method used in this research is to use the Data Mining Decission Tree classification method C4.5 algorithm where the data source used uses questionnaire technique through a google form filled out by students in the Prof. University environment. Dr. Hazairin, SH. The variables used are service quality, information quality, system quality, and performance expectations. From the analysis process, it can be seen that the level of service quality, namely service speed and staff consistency in providing services is the most dominant in determining the level of student satisfaction at the University Prof. Dr. Hazairin, SH. It is hoped that the results of this research can be used for the purposes of evaluating higher education policies in improving the quality of services in the academic and student fields